PEGylated sequence-controlled macromolecules using supramolecular binding to target the Taspase1/Importin α interaction. Issue 25 (24th February 2021) - Pasch, Peter; Höing, Alexander; Ueclue, Serap; Killa, Matthias; Voskuhl, Jens; Knauer, Shirley K.; Hartmann, Laura
Abstract : PEGylated sequence-controlled macromolecules using supramolecular binding motifs effectively disrupt Taspase1 interaction with Importin α in a concentration-dependent manner, thereby exploiting a novel inhibition mechanism for this protease. Abstract : A novel strategy to inhibit the oncologically relevant protease Taspase1 is explored by developing PEGylated macromolecular ligands presenting the supramolecular binding motif guanidiniocarbonylpyrrole (GCP). Taspase1 requires interaction of its nuclear localization signal (NLS) with import receptor Importin α. We show the synthesis and effective interference of PEGylated multivalent macromolecular ligands with Taspase1–Importin α-complex formation.